Cephalometric Approach to Vertical Facial Height - Maskey, Suvit; Shrestha, Rosha (Orthodontic Journal of Nepal, 2019)
Introduction: The vertical heights and the proportions are very important for balance of the face and attractiveness along with the good smile. Harmonious vertical proportions and the Antero-posterior relations contribute to aesthetics. Therefore it is necessary to determine the vertical facial height and the ratios in treatment planning of the patients. The aims and objectives of this study are to compare the vertical facial heights of patients considering the Lower Anterior Facial Height (LAFH), the Upper Anterior Facial Height (UAFH), Total Anterior Facial Height (TAFH) and Posterior Facial Height (PFH) among the sexes in Class I skeletal group obtained from cephalometric analysis. Materials & Method: The study material comprised of 52 patients (24 males and 28 females) and lateral cephalometric radiographs were traced with Skeletal Class I relationship. Cephalometric analysis was performed by using hand tracing. Independent t tests were used for comparisons. Result: The total anterior facial height (TAFH), lower anterior facial height (LAFH), upper anterior facial height (UAFH), total posterior facial height (TPFH) measurements showed no significant differences between both sexes in Skeletal Class I group but statistically significant difference in ratios of posterior facial height and total anterior facial height and also there was statistically significant differences in the ratio between upper facial height and the total anterior facial height (p value <0.05). Conclusion: This cephalometric analysis can be applied to determine the vertical height of occlusion which can be helpful in prosthetic rehabilitation of edentulous patients.